Perbedaan Tingkat Pengetahuan Tentang Faktor Predisposisi Gangguan Jiwa Antara Sebelum dan Sesudah Diberikan Psikoedukasi Pada Remaja di Desa Nguter - Fajar Sodiq, Muhammad; , Arum Pratiwi,S.Kp., M.Kes; , Wachidah Yuniartika, S.Kep., Ners (2015)
One of the important factor to prevent increasing of mental illness is how to manage them. The teenager is part of the crucial things that role in preventing of mental illness. So they need to have knowledge about prevention of mental illness. This study purpose to analyze the influence of psychoeducation toward the level of knowledge on teenagers. The design of study of quantitative with pre experimental methods. A sample of the research is number 30 teenagers, technique sampling of this research is purposive sampling. The collect of data used questioner level of knowledge and the data analyses utilized Wilcoxon Rank Test. The result of the research shows that there were different the level knowledge between before and after study with the significance value 0, 0001.